Development of test rig for knee pad - Mohd Yusri, Shamsuddin (2012)
This is project is about to development the test rig for knee pads. The purpose of this project is to improve the performance of knee pad, automatically will increase the safety of the product. Finished components can have very different impact performance depends on the material that have used to create it. The application of pneumatic system is using for this test rig in order to get the impact force. By using this system, impact force can be manipulated into a different level. This system also can constant the time impact in order to get a more accurate data to analyze. Finished knee pad must be test with test rig whether it can work as expected. The use of light and toughness material is applied in order to develop this test rig that have capability and performance as well as to reduce the cost of the project. This project has gives more knowledge about the mechanical properties and machining process. Besides that, it can help student to study about impact force at the certain protective equipment especially knee pad. The design and fabrication of this knee pad test rig hopefully can be reference to develop a larger and more complex design knee pad test rig in future.